2020
DOI: 10.3390/agronomy10091388
|View full text |Cite
|
Sign up to set email alerts
|

Indigo as a Plant Growth Inhibitory Chemical from the Fruit Pulp of Couroupita guianensis Aubl.

Abstract: Weed management is an important issue since weeds directly compete with crop plants for space, nutrients; serve as habitat for insect pests and diseases, and can create a significant annual reduction in crop productivity. This study focused on evaluating the contribution of the secondary metabolites of the fruit pulp of Couroupita guianensis Aubl. for its potential growth inhibitory effect. Crude extracts of C. guianensis fruit pulp were collected with different solvents and applied to test plants in petri dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…This AgNP preparation had an approximate diameter of 4.5 nm with a spherical shape, which indicated that it was a good model to accurately describe the AgNP atomistic structure and its interactions with the molecules in the plant extract. To load the AgNP with the molecules commonly found in the plant extract of C. guianensis, we chose five molecules whose atomistic structures are reported in Figure 2: Couroupitine A, indigo, idirubin, nerol and isatin [51]. The structure of the AgNP obtained in the first step was inserted into the center of an empty cubic box that was 9 nm in size.…”
Section: Molecular Dynamics Simulations(mds)mentioning
confidence: 99%
See 3 more Smart Citations
“…This AgNP preparation had an approximate diameter of 4.5 nm with a spherical shape, which indicated that it was a good model to accurately describe the AgNP atomistic structure and its interactions with the molecules in the plant extract. To load the AgNP with the molecules commonly found in the plant extract of C. guianensis, we chose five molecules whose atomistic structures are reported in Figure 2: Couroupitine A, indigo, idirubin, nerol and isatin [51]. The structure of the AgNP obtained in the first step was inserted into the center of an empty cubic box that was 9 nm in size.…”
Section: Molecular Dynamics Simulations(mds)mentioning
confidence: 99%
“…The obtained box was then filled with SPC water [52]. The system was simulated at 300 K for 100 ns while the Ag atoms positions were kept frozen, as was carried out previously [51][52][53][54]. The Gromos 54a7 force field was employed for the simulation of the adsorption of molecules over the AgNP surface [55][56][57].…”
Section: Molecular Dynamics Simulations(mds)mentioning
confidence: 99%
See 2 more Smart Citations
“…Indigo was used to dye silk fabrics unearthed from the Western Han Dynasty tomb in Mawangdui, Changsha. Silk and cotton printing and dyeing products of the Tang Dynasty are preserved in Shosakura in Xinjiang and Japan, including batik cotton fabric with blue background and white flower [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%